UPAYA PENINGKATAN HASIL BELAJAR PASING BAWAH BOLA VOLI DENGAN PENDEKATAN BERMAIN PADA SISWA KELAS X MAN DEMAK - Ramadhana, Indrianto Arif; Perdana, Jeff Agung (Jurnal Ilmiah Bina Edukasi, 2020)
Forearm pass is one of the materials that must be mastered by students of class X Senior High School. In fact, many students do not yet master and know forearm pass techniques. This research is a classroom action research (CAR) with two cycles. Each cycle consists of 4 stages, namely: planning, action, observation and reflection. Data collection was carried out using observations and questionnaires. Data were analyzed using Hake's Normalized Gain formula. From the results of the study it is known that the psychomotor domain of students increased by 0.42 with average criteria from cycle 1 to cycle 2. The affective domain increased by 0.37 with average criteria. The cognitive domain increased by 0.39 with average criteria. Based on the results of the data analysis, it can be concluded that learning forearm pass techniques with games method can improve student learning outcomes.